THE UNPRECEDENTED VIABLE IN THE TRAINING OF TEACHER OF BASIC EDUCATION: FREIREAN KNOWLEDGE AND ETHICAL PRINCIPLES - Lima Coimbra, Camila (Revista Ciranda, 2022)
This work reports the experiences lived in the educational praxis of the Freirean Ethical Principles discipline, which is optional for the Licentiate Courses and offered by the Faculty of Education of the Federal University of Uberlândia. This praxis was anchored in some categories of Freire’s philosophy of education, from the generative words created by the classes that participated in its development. Thus, it becomes the objective of this work to reveal the “viable novels” that were built in this praxis. How to break with a disciplinary logic? What to think about such fragmented times and university spaces? What are the challenges for a Freirean praxis? How to learn theory and practice from a Freirean perspective? How to experience a Freirean praxis in such a rigid structure? What “viable novels” built? Problematizations that were pursued throughout this educational praxis, in order to justify the worked categories: politics, commitment, ethics, democracy and dialogicity, in addition to the relationships with an educational praxis developed collectively. The need for a shared praxis in a rigorous and loving teaching exercise, in search of perspectives for the formation of teachers for Basic Education, was also addressed.